“Estrategias para el control de enfermedades fungosas en piñón blanco (jatropha curcas L.) en picota- San Martín – Perú” - Murrieta Salas, Juvenal (2014)
The present work titled "Strategies for the control of fungous illnesses in white pinenut (Jatropha curcas l.) in Pillory-San Martín; he/she has as main objective to carry out strategies for the handling of fungous illnesses in white Pinenut; to identify mushrooms fitopatogenos in the pinenut plants, to apply cultural works that reduce the incidence, severity of the fungous illnesses and to evaluate the different control strategies with fungicides looking for the effectiveness to obtain bigger yield at smaller cost. The investigation work was carried out in the CC. PP Leoncio Prado, located in the district of Tingo of Ponasa, county Pillory, department of San Martin. In a period of 18 months. The Desing of Blocks was used totally at random with 15 treatments and 3 repetitions; it was used systemic fungicides and protectants. The samples analyzed in the laboratory of Fitopatologia of the UNSM-T, the following fungous illnesses Roya Phakopsora sp was identified; Antracnosis Col/etotrichum gloeosporoide and Botrytis Botryotinia cinerea; the best used strategy was the treatament 11 (sulfate of copper pentahidratado 0,025%0) and the treatament 3 (Metalaxil + Mancozeb 2,5%o & Benomil 0,75%0), due that showed bigger yield in both prunings; they also controlled relatively to the illnesses as much in incidence as in severity, with the sanitary pruning and the control strategies with fungicides were possible to reduce to the minimum to the Roya of the whithe pinenut, also the result of the analysis of benefit cost in both prunings, did not orne out satisfactorily because the maintenance cost turned oud to be negative with concerning the yields of each treatment.